Effect of plasma free fatty acids on lung function in male COPD patients - Rostam Yazdani; Hossein Fallah; Shirin Yazdani; Beydolah Shahouzehi; Behnaz Danesh (Scientific Reports)
Abstract Inflammation and oxidative stress play a pivotal role in COPD pathogenesis. Free fatty acids (FFA) as signaling molecules through a series of G-proteins coupled receptors, play an important role in regulation of the immune system and oxidative stress. For this reason, we decided to investigate the profile of FFA in the plasma in the COPD patients. This is a case-control study comparing 40 male patients with COPD and 40 healthy controls. Biochemical plasma parameters were measured by Autoanalyzer, Malondialdehyde by TBA, total antioxidant capacity via FRAP method and the concentration of free fatty acids were measured by gas chromatography. Then the relationship between the data and the spirometric findings of the patients was determined. In male COPD patients, fasting glucose, myristic acid, palmitic acid, stearic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid and total FFA showed a significant difference with the control group. Also, a positive correlation between the medium chain FFA and lung function was observed. The results of the present study showed that the concentration of different free fatty acids is different in healthy people and male COPD patients, and these differences, especially in the case of medium and long chain fatty acids, can be related to the lung function.